Community decision making based on social capital during COVID-19 pandemic: Evidence from Bangelan Village tourism, Indonesia - Gunawan Prayitno; Dian Dinanti; Rahmawati Rahmawati; Lusyana Eka Wardhani; Aidha Auliah (Publisher of Widyagama University of Malang (UWG Press), 2022)
Bangelan is one of the villages which proclaim as a tourism village in Malang Regency. However, the COVID-19 pandemic has impacted tourist visits, causing considerable losses to tourism economic activityr. This study aims to determine the structure of community adaptation in the face of the COVID-19 pandemic, which is associated with social capital and collective actions to restore socioeconomic conditions. Assessment of social capital used three variables: trust, social norms, and social networks, each of which identifies its relationship with collective action. This study used descriptive analysis and Structural Equation Modeling (SEM) and the data were obtained from the questionnaire. The study results explain that the norm variable in social capital wasthe most influential for the community to make decisions in taking collective action to restore the socioeconomic conditions. The norms were based on compliance with applicable norms and social sanctions against those who violate. Social norms affected almost every aspect of people's lives and became development pillars. The success of development efforts depended on conforming to or contradicting the development with pre-existing norms. In addition, the role of the community as hosts was the most important element in tourism development where they lived. Furthermore, norms could prevent outsiders from taking the opportunities that often dominate the development of local tourism destinations.JEL Classification I32; R23; R51